National Geographic little kids first big book of animals - "Hughes, Catherine D." (Washington D. C., 2010)
The National Geographic Little Kids First Big Book of Animals is an adorable animal reference sure to be welcomed by parents and librarians alike. Filled with fluffy and scaly creatures big and small, this appealing book introduces the youngest explorers to the world of wildlife, using a child-friendly format inspired by the blockbuster National Geographic Little Kids magazine. This exciting new reference for the very young mirrors the magazine?s square shape, readable fonts, and fun content, to keep little ones thrilled with every colourful page. Little Kids First Big Book of Animals devotes four pages each to 32 high-interest creatures, including dolphins, tigers, butterflies, frogs, penguins, wolves, and pandas. More than 150 of National Geographic?s most charming animal photos illustrate the profiles, which feature just the kind of facts that little kids want to know?the creature?s size, diet, home, and more. Child-friendly text explains how animal parents take care of their young, how baby animals change as they grow, and how they learn to hunt and eat. The brief text, large type, and appealing profiles are perfect for young readers to enjoy on their own, or for parents and other caregivers to read aloud. These animal tales will quickly become favourites at Storytime, bedtime, and any other time.